Synthesis and antimicrobial activity of 1H-1,2,3-triazole and carboxylate analogues of metronidazole - Avula, Satya Kumar; Raza Shah, Syed; Al-Hosni, Khdija; U. Anwar, Muhammad; Csuk, Rene; Das, Biswanath; Al-Harrasi, Ahmed (Beilstein Journal of Organic Chemistry, 2021)
Herein, a series of novel 1H-1,2,3-triazole and carboxylate derivatives of metronidazole (5a–i and 7a–e) were synthesized and evaluated for their antimicrobial activity in vitro. All the newly synthesized compounds were characterized by 1H NMR, 13C NMR, HRMS, and 19F NMR (5b, 5c and 5h) spectroscopy wherever applicable. The structures of compounds 3, 5c and 7b were unambiguously confirmed by single crystal X-ray analysis diffraction method. Single crystal X-ray structure analysis supported the formation of the metronidazole derivatives. The antimicrobial (antifungal and antibacterial) activity of the prepared compounds was studied. All compounds (except 2 and 3) showed a potent inhibition rate of fungal growth as compared to control and metronidazole. The synthetic compounds also showed higher bacterial growth inhibiting effects compared to the activity of the parent compound. Amongst the tested compounds 5b, 5c, 5e, 7b and 7e displayed excellent potent antimicrobial activity. The current study has demonstrated the usefulness of the 1H-1,2,3-triazole moiety in the metronidazole skeleton.
Keywords: antimicrobial agents; carboxylate analogues; 1H-1,2,3-triazole analogues; metronidazole; synthesis

(untitled) - Löfmark, S.; Edlund, C.; Nord, C. E. (Clin. Infect. Dis., 2010)

(untitled) - Freeman, C. D.; Klutman, N. E.; Lamp, K. C. (Drugs, 1997)

(untitled) - Abdel-Wahab, B. F.; Abdel-Latif, E.; Mohamed, H. A.; Awad, G. E. A. (Eur. J. Med. Chem., 2012)

(untitled) - Singh, N.; Pandey, S. K.; Tripathi, R. P. (Carbohydr. Res., 2010)

(untitled) - Thirumurugan, P.; Matosiuk, D.; Jozwiak, K. (Chem. Rev., 2013)

Comprehensive Heterocyclic Chemistry II - Fan, W. Q.; Katritzky, A. R. (Elsevier, 1996)

(untitled) - Dubey, S.; Jain, V.; Precthi, G. B. (Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem., 2009)

(untitled) - Wardman, P. (Br. J. Radiol., 2018)

(untitled) - Rocha-Garduño, G.; Hernández-Martínez, N. A.; Colín-Lozano, B.; Estrada-Soto, S.; Hernández-Núñez, E.; Prieto-Martínez, F. D.; Medina-Franco, J. L.; Chale-Dzul, J. B.; Moo-Puc, R.; Navarrete-Vázquez, G. (Molecules, 2020)

(untitled) - Valdez, C. A.; Tripp, J. C.; Miyamoto, Y.; Kalisiak, J.; Hruz, P.; Andersen, Y. S.; Brown, S. E.; Kangas, K.; Arzu, L. V.; Davids, B. J.; Gillin, F. D.; Upcroft, J. A.; et al. (J. Med. Chem., 2009)

(untitled) - Faghih-Mirzaei, E.; Sabouri, S.; Zeidabadinejad, L.; AbdolahRamazani, S.; Abaszadeh, M.; Khodadadi, A.; Shamsadinipour, M.; Jafari, M.; Pirhadi, S. (Bioorg. Med. Chem., 2019)

(untitled) - Rami, M.; Dubois, L.; Parvathaneni, N.-K.; Alterio, V.; van Kuijk, S. J. A.; Monti, S. M.; Lambin, P.; De Simone, G.; Supuran, C. T.; Winum, J.-Y. (J. Med. Chem., 2013)

(untitled) - Kumar, L.; Jain, A.; Lal, N.; Sarswat, A.; Jangir, S.; Kumar, L.; Singh, V.; Shah, P.; Jain, S. K.; Maikhuri, J. P.; Siddiqi, M. I.; Gupta, G.; et al. (ACS Med. Chem. Lett., 2012)

(untitled) - Upadhyay, A.; Chandrakar, P.; Gupta, S.; Parmar, N.; Singh, S. K.; Rashid, M.; Kushwaha, P.; Wahajuddin, M.; Sashidhara, K. V.; Kar, S. (J. Med. Chem., 2019)

(untitled) - Avula, S. K.; Khan, A.; Rehman, N. U.; Anwar, M. U.; Al-Abri, Z.; Wadood, A.; Riaz, M.; Csuk, R.; Al-Harrasi, A. (Bioorg. Chem., 2018)

(untitled) - Avula, S. K.; Khan, A.; Halim, S. A.; Al-Abri, Z.; Anwar, M. U.; Al-Rawahi, A.; Csuk, R.; Al-Harrasi, A. (Bioorg. Chem., 2019)

(untitled) - Yadav, J. S.; Thrimurtulu, N.; Uma Gayathri, K.; Subba Reddy, B. V.; Prasad, A. R. (Tetrahedron Lett., 2008)

(untitled) - Baran, P. S.; Zografos, A. L.; O'Malley, D. P. (J. Am. Chem. Soc., 2004)

(untitled) - Huisgen, R. (Angew. Chem., Int. Ed. Engl., 1963)

(untitled) - Bera, S.; Linhardt, R. J. (J. Org. Chem., 2011)

(untitled) - Xu, S.; Held, I.; Kempf, B.; Mayr, H.; Steglich, W.; Zipse, H. (Chem. – Eur. J., 2005)

(untitled) - Höfle, G.; Steglich, W.; Vorbrüggen, H. (Angew. Chem., Int. Ed. Engl., 1978)